TYPOLOGICAL AND SEMANTIC FEATURES OF TYPOLOGICAL AND SEMANTIC FEATURES OF TERM FORMATION IN ENGLISH AND UZBEK LANGUAGES A COMPARATIVE LINGUISTIC RESEARCH (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article presents a comparative analysis of term formation in English and Uzbek, focusing on morphological and semantic aspects. The study explores how each language constructs terminology in fields such as education, law, and science. Using a qualitative methodology and data from corpora, dictionaries, and academic texts, the research reveals that English primarily relies on compounding, affixation, and borrowing, while Uzbek favors agglutination and native derivation. Semantically, English terms often carry abstract or metaphorical meanings, whereas Uzbek terms tend to be concrete and culturally rooted. The findings contribute to a deeper understanding of the linguistic and cultural mechanisms underlying terminology formation in both languages, and offer valuable insights for translation, lexicography, and bilingual education.